2017
DOI: 10.3906/bot-1610-24
|View full text |Cite
|
Sign up to set email alerts
|

Foliar applications of alpha-tocopherol improves the composition of fresh pods of Vigna radiata subjected to water deficiency

Abstract: Alpha-tocopherol (α-Toc), so-called vitamin E, is a low molecular weight lipophilic antioxidant that generally protects plants from stress-induced cellular oxidation. It is well known that exogenously applied α-Toc is effective in improving plant growth and developmental processes under adverse environmental conditions. The current study was performed to determine the best concentration of α-Toc [0 (no spray), 100, 200, and 300 mg L -1 ] that could improve the biological yield and chemical constituents of fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
4
12
0
Order By: Relevance
“…However, it is well reported that plants modulate their physio-biochemical processes and anatomical features according to the internal or external climate so as to survive under such harsh conditions (Shafiq et al, 2015;Akram et al, 2016). In the present study, plant growth measured as shoot and root dry weights of both oat cultivars decreased under water deficit conditions, which is in agreement with some earlier findings which also reported a water stress-induced decline in growth of various crops such as wheat (Jatoi et al, 2011;Raza et al, 2012), mungbean (Sadiq et al, 2017), sugar beet (Bloch et al, 2006), grasses (Akram et al, 2007), maize (Zhang et al, 2012) and radish (Akram et al, 2015). They found that water stress-reduced plant growth is linked to the interior status of the plant with respect to specifically photosynthesis, nutrients, hormones, antioxidants, primary and secondary metabolites, fluorescence, quantum use efficiency, respiration, and photosynthetic pigments, etc.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, it is well reported that plants modulate their physio-biochemical processes and anatomical features according to the internal or external climate so as to survive under such harsh conditions (Shafiq et al, 2015;Akram et al, 2016). In the present study, plant growth measured as shoot and root dry weights of both oat cultivars decreased under water deficit conditions, which is in agreement with some earlier findings which also reported a water stress-induced decline in growth of various crops such as wheat (Jatoi et al, 2011;Raza et al, 2012), mungbean (Sadiq et al, 2017), sugar beet (Bloch et al, 2006), grasses (Akram et al, 2007), maize (Zhang et al, 2012) and radish (Akram et al, 2015). They found that water stress-reduced plant growth is linked to the interior status of the plant with respect to specifically photosynthesis, nutrients, hormones, antioxidants, primary and secondary metabolites, fluorescence, quantum use efficiency, respiration, and photosynthetic pigments, etc.…”
Section: Discussionsupporting
confidence: 92%
“…They found that water stress-reduced plant growth is linked to the interior status of the plant with respect to specifically photosynthesis, nutrients, hormones, antioxidants, primary and secondary metabolites, fluorescence, quantum use efficiency, respiration, and photosynthetic pigments, etc. (Ashraf and Harris, 2013;Sadiq et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps this may be due to the role of vitamins as co -enzyme in an enzymatic cofactor and plant growth regulator (Gomez and Lajolo, 2008). These findings are in agreement with those reported by El-Bassiouny et al (2005), Al-Qubaie (2012) and Sadiq et al (2017).…”
Section: Flowering Characteristicssupporting
confidence: 94%
“…Results showed that combination of EM+V.C+V.E increased CAT, APX at chilly storage. likewise, (Sun et al,2010) reported Ascorbic acid ,CH increased CAT,APX ; (Liu et al ., 2014 ) reported that Plums treated with ascorbic acid showed significantly excessive CAT activity during the entire storage period .Also (Sadiq et al, 2017) reported that externally applied 200 and 300 mg L -1 α-Toc significantly increased the activities of antioxidative enzymes (SOD, POD, and CAT). The formation and function of membranes are influenced and some oxidation products such as malondialdehyde (MDA) are presented that react with biomolecules and exert cytotoxic and genotoxic effects.…”
Section: Catalase Activity and Ascorbate Peroxidasementioning
confidence: 99%